Depression and Antidepressants During Pregnancy: Craniofacial Defects Due to Stem/Progenitor Cell Deregulation Mediated by Serotonin - Sánchez, Natalia; Juárez-Balarezo, Jesús; Olhaberry, Marcia; González-Oneto, Humberto; Muzard, Antonia; Mardonez, María Jesús; Franco, Pamela; Barrera, Felipe; Gaete, Marcia (Frontiers in Cell and Developmental Biology, 2021)
Depression is a common and debilitating mood disorder that increases in prevalence during pregnancy. Worldwide, 7 to 12% of pregnant women experience depression, in which the associated risk factors include socio-demographic, psychological, and socioeconomic variables. Maternal depression could have psychological, anatomical, and physiological consequences in the new-born. Depression has been related to a downregulation in serotonin levels in the brain. Accordingly, the most commonly prescribed pharmacotherapy is based on selective serotonin reuptake inhibitors (SSRIs), which increase local serotonin concentration. Even though the use of SSRIs has few adverse effects compared with other antidepressants, altering serotonin levels has been associated with the advent of anatomical and physiological changes in utero, leading to defects in craniofacial development, including craniosynostosis, cleft palate, and dental defects. Migration and proliferation of neural crest cells, which contribute to the formation of bone, cartilage, palate, teeth, and salivary glands in the craniofacial region, are regulated by serotonin. Specifically, craniofacial progenitor cells are affected by serotonin levels, producing a misbalance between their proliferation and differentiation. Thus, it is possible to hypothesize that craniofacial development will be affected by the changes in serotonin levels, happening during maternal depression or after the use of SSRIs, which cross the placental barrier, increasing the risk of craniofacial defects. In this review, we provide a synthesis of the current research on depression and the use of SSRI during pregnancy, and how this could be related to craniofacial defects using an interdisciplinary perspective integrating psychological, clinical, and developmental biology perspectives. We discuss the mechanisms by which serotonin could influence craniofacial development and stem/progenitor cells, proposing some transcription factors as mediators of serotonin signalling and craniofacial stem/progenitor cell biology. We finally highlight the importance of non-pharmacological therapies for depression on fertile and pregnant women, and provide an individual analysis of the risk-benefit balance for the use of antidepressants during pregnancy.